Spatiotemporal Evolution and Attribution of Groundwater in Wuzhi Region - Huang, Shixin; Li, Xiaodong (International Journal of Natural Resources and Environmental Studies, 2026)
Based on groundwater observation data from the Wuzhi area during 2000–2023, this study integrated the Mann–Kendall trend test, geostatistical analysis, and principal component analysis to investigate the spatiotemporal evolution and driving mechanisms of the groundwater flow field. The results show that during the study period, the groundwater depth generally increased, with a slightly larger rise in the dry season than in the wet season. The groundwater level exhibited a spatial pattern of being higher in the northwest and lower in the southeast, and declined continuously over time. Human activities were the main cause of anomalous changes in the groundwater flow field, with agricultural irrigation and groundwater extraction playing dominant roles. Spatially, groundwater depth decreased from the alluvial zone of the Yellow River and Qin River in the west to the Yellow River alluvial plain in the southeast. The reduction in groundwater storage was primarily due to increased extraction driven by rising irrigation water use, whose impact far exceeded that of natural factors. Sustainable management of agricultural water resources is essential for ensuring groundwater security in this region.